The holy land reborn : pilgrimage & the Tibetan reinvention of Buddhist India. - Huber, Toni (Buddhism and modernity, 2008)
The Dalai Lama has said that Tibetans consider themselves “the child of Indian civilization” and that India is the “holy land” from whose sources the Tibetans have built their own civilization. What explains this powerful allegiance to India? In The Holy Land Reborn¸ Toni Huber investigates how Tibetans have maintained a ritual relationship to India, particularly by way of pilgrimage, and what it means for them to consider India as their holy land. Focusing on the Tibetan creation and recreation of India as a destination, a landscape, and a kind of other, in both real and idealized terms, Huber explores how Tibetans have used the idea of India as a religious territory and a sacred geography in the development of their own religion and society. In a timely closing chapter, Huber also takes up the meaning of India for the Tibetans who live in exile in their Buddhist holy land. A major contribution to the study of Buddhism, The Holy Land Reborn describes changes in Tibetan constructs of India over the centuries, ultimately challenging largely static views of the sacred geography of Buddhism in India -- Présentation de l'éditeur.